Revision of the Astyanax orthodus species-group (Teleostei: Characidae) with descriptions of three new species - Riuz-C, Raquel I.; Román-Valencia, César; Taphorn, Donald C.; Buckup, Paulo A.; Ortega, Hernán (European Journal of Taxonomy, 2018)
The Astyanax orthodus species-group includes nine species: Astyanax boliviensis sp. nov., A. bopiensis nom. nov., A. embera sp. nov., A. gandhiae sp. nov., A. moorii comb. nov., A. orthodus, A. superbus, A. villwocki and A. yariguies comb. nov. The group is diagnosed by the presence of a series of pinnate-shaped marks (chevrons) located along the lateral midline, which extends from the humeral region to the caudal peduncle. Astyanax bopiensis nom. nov. is proposed as a substitute name for Astyanacinus multidens, which, along with Astyanax yariguies comb. nov., we reassign to Astyanax.We also propose the synonymy of Astyanacinus with Astyanax. The members of the A. orthodus species-group are distributed in northwestern South America, occurring in the Patia River drainage (A. embera sp. nov.) of the Pacific coast of Colombia, the Atrato River Basin (A. orthodus), the Magdalena River Basin (A. yariguies comb. nov.) of Caribbean Colombia, streams of the southern flank of the Andes of the Orinoco Basin in Venezuela (A. superbus), in the upper Amazon River Basin of Colombia, Ecuador and Peru (A. villwocki, A. gandhiae sp. nov.), from the upper Paraguay River (A. moorii comb. nov.), the Madidi and Mamore Rivers, Bolivia (A. boliviensis sp. nov. and A. bopiensis nom. nov.). All species currently included in Astyanacinus are reassigned to the Astyanax orthodus species-group.